2017
DOI: 10.18203/2320-1770.ijrcog20175237
|View full text |Cite
|
Sign up to set email alerts
|

Common gynecological morbidities among married women in a resettlement colony of East Delhi

Abstract: Background: A women is always celebrated for child birth but gynaecological issues a stigma is attached. The fear of being ostracised by the society for gynaecological problems is deep set. Gynaecological morbidity is defined as “structural and functional disorder of genital tract not related to pregnancy, delivery or perpuerium”. This paper aims to study the pattern of gynaecological morbidity among married women residing in a resettlement colony of East Delhi.Methods: A community based cross-sectional study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 2 publications
2
4
0
Order By: Relevance
“…The predominant gynaecological complaint among the study population was lower back ache (77.6%) followed by white discharge per vagina (29.0%) and menstrual problems (25.8%). Gynaecological complaints reported in previous studies are similar to our study, though the proportion may vary [ 14 , 17 , 18 , 20 , 22 , 23 ].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The predominant gynaecological complaint among the study population was lower back ache (77.6%) followed by white discharge per vagina (29.0%) and menstrual problems (25.8%). Gynaecological complaints reported in previous studies are similar to our study, though the proportion may vary [ 14 , 17 , 18 , 20 , 22 , 23 ].…”
Section: Discussionsupporting
confidence: 90%
“…In our study, majority of the women had three or more gynaecological complaints (74.6%). The higher number of gynaecological complaints among the study population may be attributed to the lack of awareness regarding gynaecological morbidities, poor accessibility to healthcare facilities in remote areas, embarrassment, stigma and fear towards pelvic examination, and above all the prevailing patriarchal family system in rural India, as indicated in prior studies [ 4 , 7 , 17 , 20 ]. The predominant gynaecological complaint among the study population was lower back ache (77.6%) followed by white discharge per vagina (29.0%) and menstrual problems (25.8%).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The most commonly reported gynecological problems were menstrual disorders such as menorrhagia and dysmenorrhea. Similar results were obtained in studies done by Mathew et al and Mathur et al [1013] Urinary tract infections and reproductive tract infections [UTI and RTI] were the most commonly diagnosed gynecological morbidity with prevalence of 14% and 11.6%, respectively. Studies done by Srikala et al and Muthulakshmi et al , the prevalence of UTI was found to be 12.4% and 20.4%, respectively.…”
Section: Discussionsupporting
confidence: 89%
“…Study done by Mansi et al found the prevalence of RTI to be 8.1%. [13] This shows that UTI and RTI are more common among married women when compared with other gynecological problems.…”
Section: Discussionmentioning
confidence: 99%